The efficacy of mitochondrial targeting antiresistant epirubicin liposomes in treating resistant leukemia in animals - Men Y (Dove Medical Press, 2011)
Ying Men*, Xiao-Xing Wang*, Ruo-Jing Li, Yan Zhang, Wei Tian, Hong-Juan Yao, Rui-Jun Ju, Xue Ying, Jia Zhou, Nan Li, Liang Zhang, Yang Yu, Wan-Liang LuState Key Laboratory of Natural and Biomimetic Drugs, and School of Pharmaceutical Sciences, Peking University, Beijing, People's Republic of China*These authors contributed equally to this manuscriptBackground: Multidrug resistance (MDR) of cancers can be circumvented by inducing programmed cell death, which is known as apoptosis. Mitochondria play a crucial role in apoptosis. Mitochondria-specific therapy would provide an efficient strategy for treating resistant cancers.Design and methods: A strategy was proposed here to overcome MDR by designing cancer mitochondria-specific drug-loaded liposomes, namely, antiresistant epirubicin mitosomes, aimed at treating resistant leukemia by targeting mitochondria. Evaluations were performed on human chronic leukemia K562, MDR K562/ADR cells, and female BALB/c nude mice xenografted with MDR K562/ADR cells. The liposomes were characterized through assays of cytotoxicity, mitochondrial targeting, caspase-9 and caspase-3, antitumor activities, and TUNEL (terminal deoxynucleotidyl transferase dUTP nick end labeling) analysis.Results: The average size of antiresistant epirubicin mitosomes was in the range of 105–115 nm. Antiresistant epirubicin mitosomes were effective in inhibiting proliferation of MDR K562/ADR cells in vitro and selectively accumulated into the mitochondria. Caspase-9 and caspase-3 activity was increased after applying antiresistant epirubicin mitosomes. In xenografted resistant MDR K562/ADR tumor in nude mice, antiresistant tumor effect of antiresistant epirubicin mitosomes was evidently observed. Apoptotic inducing effects by antiresistant epirubicin mitosomes were noticeably evidenced via mitochondrial pathway.Conclusions: Antiresistant epirubicin mitosomes had significant inhibitory effect against resistant leukemia in vitro and in vivo, hence providing a promising strategy for improving therapeutic efficacy in resistant human leukemia.Keywords: mitosomes, mitochondria signaling pathway, nude mice